Faktor Risiko Penderita Glaukoma Primer Di RSUD TARAKAN Tahun 2021-2022 - Leonardo, Vanessa Katherine; Farfar, Iggrid Osya; Silaen, Desi Hartati (Universitas Kristen Krida Wacana, 2025)
Glaucoma is an optic neuropathy resulting from intraocular pressure that is above average, and is synonymous with visual field disorders and optic nerve papillary atrophy. Glaucoma is asymptomatic so sudden blindness or sudden loss of visual field often occurs in glaucoma patients. Purpose : The main focus of this research is to identify factors related to glaucoma sufferers at Tarakan District Hospital in 2021-2022. Methods : This research used a purposive sampling technique with a cross sectional method with 30 respondents. Data collection was carried out from September to October. Results : The results of this study showed that there was no relationship between age (p=1,000), gender (p=0.689), unilateral intraocular pressure (p= 0.221), bilateral intraocular pressure (p= 1,000), and history of systemic disease (p= 1,000) towards primary glaucoma sufferers at TARAKAN Regional Hospital. Conclusion: The conclusion from this study was that there was no relationship between age, gender, intraocular pressure, and history of systemic disease on the incidence of glaucoma at TARAKAN Regional Hospital. My advice as a researcher is that people who are at high risk of developing glaucoma should routinely undergo comprehensive eye examinations.